NAKHODA KMP SENOPATI NUSANTARA DITINJAU DART SEGI HUKUM - Gatot Teguh Rusliyanto (Widyariset, 2009)
KM Senopati was sinking on the passage from Kumai Kalimantan to Tanjung Emas Semarang, at Jepara north beach, Central Java on 29 December 2006. There were around 545 passengers on board in this accident in which hundreds of them lost their lives. Theory of sea transportation found that human errorf actor was the one of the causes in this casualties. At KMP SENOPATI NUSANTARA was found various awkwardness though the ship had been assumed seaworthinesxs. Intention of this research is to know any negligence factors of the Captain at KM. Senopati Nusantara casualties. The approach method applied is approach of jurisdictionalsociologist and specification of research applied is descriptive analysis qualitatively. Data used at this research are primary and secondary data. Based on the result, negligence aspect is one of the many factors of KM Senopati Nusantara casualties. Captain was guilty because of his negligence causing many people died and performed within implementing position as occupation.